WISATA KULINER DI PANTAI INDAH KAPUK - Vina Angelina; Mieke Choandi (Jurusan Arsitektur dan Perencanaan, 2019)
At millennial era, trends are very easily spread due to the presence of social media. Millennials with high curiosity, as